A Threshold Panel Model Study on the Impact of Coal Resources on Economic Growth in China - Wang, Zilin; Burlakov, Georgi; Mach, Petr, 1975-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2024)
This thesis investigates the economic phenomenon known as the 'resource curse' using panel data from 18 coal-reliant cities in China, covering the years 2006 to 2016. Despite China’s status as the world's leading consumer and producer of coal, certain regions exhibit signs of the resource curse, where abundant natural resources do not translate into equivalent economic growth. This thesis employs a panel regression model to analyze data from the China City Statistical Yearbook, examining the relationship between natural resource dependency and economic performance at both the city and provincial levels. Our findings reveal that coal dependency significantly hampers economic growth in these cities, supporting Hypothesis 1 that natural resource reliance has a negative impact on the per capita GDP growth rate. In contrast, investments in technology and improvements in industrial structure positively correlate with economic growth, affirming Hypothesis 3 regarding the beneficial impacts of technological investments. However, the influence of human capital investment varied, with non-uniform effects across different cities; thus, Hypothesis 2 was not substantiated.
Vedoucí práce: Georgi Burlakov
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses